Innovations in Durability of Sustainable Concrete Materials - Taffese, Woubishet Zewdu; Nunes, Sandra Barbosa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Welcome to the Reprint of "Innovations in Durability of Sustainable Concrete Materials", a collection presenting cutting-edge research on sustainable and durable concrete. Discover ten insightful manuscripts exploring the various aspects of sustainable concrete technology, from novel materials to advanced modeling methods. This compilation showcases the transformative journey of the concrete industry towards a sustainable future. Join us in this paradigm-shifting exploration at the intersection of durability and sustainability.